Moacir Santos, entre a bossa nova e o “samba-jazz”: uma análise da construção do Brasil moderno através da música popular brasileira dos anos 1954-1967 - Santi, Rodrigo Giuli Orlando (2023)
The present research aims to investigate the musical journey of the composer, multi-instrumentalist, conductor, and arranger Moacir Santos (Flores, April 8, 1926 - Pasadena, August 6, 2006) as a historical and organic intellectual figure who, through instrumental music, synthesized the diverse Brazilian cultural nuances, with a focus on the regional rhythms of the Northeast, such as “baião” and “maracatu”, the latter originating from Pernambuco, the composer's hometown. By creating a wholly original aesthetic, reinterpreting “traditional” Brazilian rhythms in symphonic arrangements, redefining the boundaries between classical and popular music, blending rhythmic-melodic intentions with a harmonic approach that oscillates between tonal and modal, and engaging in musical performances that resonate with North American jazz, the maestro's “musical brain” becomes an interpretive key that shifts the historical and musical perspective on the modernization of Brazilian popular music, which had been primarily associated with a particular creative approach: the bossa nova, consecrated by the iconic trio of João Gilberto, Tom Jobim, and Vinícius de Moraes. We seek to understand the processes of inventing the Brazilian national identity through cultural institutions, music critics, and the formation of the popular music field, which began in the 1920s in dialogue with Moacir Santos' musical experience, focusing on the period from 1954 to 1967